From aging to long COVID: exploring the convergence of immunosenescence, inflammaging, and autoimmunity - Müller, Ludmila; Di Benedetto, Svetlana (Frontiers in Immunology, 2023)
The process of aging is accompanied by a dynamic restructuring of the immune response, a phenomenon known as immunosenescence. This mini-review navigates through the complex landscape of age-associated immune changes, chronic inflammation, age-related autoimmune tendencies, and their potential links with immunopathology of Long COVID. Immunosenescence serves as an introductory departure point, elucidating alterations in immune cell profiles and their functional dynamics, changes in T-cell receptor signaling, cytokine network dysregulation, and compromised regulatory T-cell function. Subsequent scrutiny of chronic inflammation, or “inflammaging,” highlights its roles in age-related autoimmune susceptibilities and its potential as a mediator of the immune perturbations observed in Long COVID patients. The introduction of epigenetic facets further amplifies the potential interconnections. In this compact review, we consider the dynamic interactions between immunosenescence, inflammation, and autoimmunity. We aim to explore the multifaceted relationships that link these processes and shed light on the underlying mechanisms that drive their interconnectedness. With a focus on understanding the immunological changes in the context of aging, we seek to provide insights into how immunosenescence and inflammation contribute to the emergence and progression of autoimmune disorders in the elderly and may serve as potential mediator for Long COVID disturbances.